Synthesis of New Some Imidazole Derivatives Containing ?-Lactam Ring (Baghdad Science Journal, 2016)
In this work 5-methylene-yl - (2-methy –oxazole-4-one) (1H) imidazole (1) were synthesized from the reaction of L-Histidine with acetic anhydride and which converted to the of 5-methylene-yl-(2-methyl 3-amino imidazole-4-one)-1H-imidazole (2) by reaction with hydrazine hydrate. Schiff bases (3-6) were synthesized from the reaction of compound (2) with different aromatic aldehyde. Reaction of compounds (3-6) with chloroacetyl chloride gives azetidinone one derivatives (7-10). These compounds were characterized by FT-IR and some of them with 1H-NMR and 13C-NMR spectroscopy.